DYNAMICS OF ISLAMIC RELIGIOUS EDUCATION INNOVATION TOWARDS IMPROVING THE QUALITY OF LEARNING AND CHARACTER DEVELOPMENT - Susanto, Deki (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic Religious Education is a vital component in forming the character and morality of individual HATI BBS Middle School students in the digital era which demands innovation in learning methods and curriculum development in order to meet the needs of the times. This article explores the dynamics of innovation in Islamic Religious Education as a key step towards improving the quality of learning and developing the character of HATI BBS Middle School students. Various aspects of innovation, including the use of information technology, interactive approaches, and contextual learning methods, are explained as efforts to adapt the curriculum to the realities of the times. A deeper understanding of the role of Islamic Religious Education in the formation of character and morality in the digital era is the focus of this research. It is hoped that the research results can make a significant contribution to students' thinking and implementation of innovation in the context of Islamic religious education to improve the quality of learning and develop students' character.